Analysis of Student Peer Assessment in The Social Aspect - Annisa, Afifah Nur (SCOPE: Journal of English Language Teaching, 2024)
Peer assessment is an assessment between students that is implemented quite effectively, so teachers can save time and energy. This research focuses on peer assessment in the affective domain, especially social aspects, namely activeness, cooperation and tolerance. To find out the results of implementing peer assessments on students to assess the affective domain of student activities, cooperation and tolerance, the author uses qualitative descriptive techniques. Researchers use observation, questionnaires, and documentation to conduct research. The analytical method used is the grounded theory method. The results of this research show that the three affective domains in social assessment, namely activeness, cooperation and tolerance, have good results as evidenced by the activeness aspect getting an average result of 96.4 percent, the cooperation aspect getting a result of 97.95 percent. , and the tolerance aspect is 99.95 percent. This data shows that these three aspects are included in the "very good" category. From the results of this data, teachers can use this alternative peer assessment for affective assessment so that the assessment runs efficiently and students are also involved in the assessment. The impact of this research lies in its contribution to the development of an efficient, involving students, and comprehensive approach in assessing the affective domain, especially in social aspects. Teachers can utilize these findings to improve their assessment practices and encourage positive social behavior among students.